Kantor Nirkabel sebagai Terobosan Budaya Kerja Baru bagi Pekerja Individual - Fauzia Latif (Humaniora, 2012)
Today’s technology much influences people’s working environment. The current technology has created a working culture that is not rigid and conventional, but a flexible working environment, in terms of working site, how to work, and the products. A wireless office with its facilities is a breakthrough for both individual worker and teams in the modern era.